(3TQM GdYhGed GdLOjOs - (3eMeO Hf HjQ Ydj Hf EScfOQ GdHQcdj GdQhej , eMjj GdOjf, J (B981 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi LYd GdYGdejf GdYGedjf aGFRjf hHYO deG cGf cJGH GdYGed GdLOjO ai GdbQjH hGdHYjO cJGHkG aGNQkG hRGNQkG SCdfi HYV CRcjGA GdWGdHjf GdQGZHjf Cf CTQMg TQMkG jMd CdaGXg s
(3BNQgG (B:s
(3EPG GdMbjbI agj eMGdg dCfg GdeQGO HGdehUhd gh Gddg GdcHjQ GdeJYGdi hCfJ NHjQ ai NJe GdcJGH HgPG GdcdGe s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdfMhs